2022
DOI: 10.1186/s43163-022-00207-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcomes of olfactory and gustatory dysfunctions in hospitalized SARS-CoV-2-infected patients

Abstract: Background The prevalence of olfactory/gustatory dysfunctions among hospitalized SARS-CoV-2-infected patients is highly variable between different studies, ranging from 5.6% in the Asian population to 86% in the European population. The study aimed to detect the prevalence and the recovery of olfactory/gustatory dysfunctions in hospitalized SARS-CoV-2-infected patients in an Egyptian tertiary care center. A total of 579 hospitalized patients were enrolled. Demographic data as well as upper resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This study describes 60 patients who complained of anosmia, and 46 (76.7%) of them were confirmed to be COVID-19 positive. The symptoms of SARS-CoV-2 infection may range from an asymptomatic state, or symptomatic (e.g., fever, cough, headache, sore throat), up to acute respiratory distress syndrome [ 2 , 11 , 12 ] anosmia or ageusia might be the only symptom of the disease [ 13 ] or even it could be a sign of reinfection with COVID-19 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study describes 60 patients who complained of anosmia, and 46 (76.7%) of them were confirmed to be COVID-19 positive. The symptoms of SARS-CoV-2 infection may range from an asymptomatic state, or symptomatic (e.g., fever, cough, headache, sore throat), up to acute respiratory distress syndrome [ 2 , 11 , 12 ] anosmia or ageusia might be the only symptom of the disease [ 13 ] or even it could be a sign of reinfection with COVID-19 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 6-month follow-up, 66% of smell/taste symptoms recovered completely, 22.1% partially, while 11.9% did not recover [ 19 ]. Mahmoud et al found that 50.6% of hospitalized COVID-19-infected patients complained of olfactory/gustatory dysfunctions, and 76.5% of them complained upper respiratory tract symptoms before olfactory/gustatory symptoms [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Viral, fungal, environmental, and host factors may be responsible for this situation. Long hospital stays, impaired host immune system function due to viral infection, and excessive glucocorticoids consumption in the management of patients with COVID-19 are the main risk factors for the increased risk of mucormycosis in patients with COVID-19 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%